Proceedings of registration of land rights (concept and characters) - Мілімко, Лариса Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In the article the concept of registration realization of rights is set forth on lot lands, position of operating legislative and regulations normatively-legal acts, looks of legislators on the basis of analysis of that maybe establishment of signs of registration realizations of rights on lot lands, is analyzed.